STUDI EVALUASI PENGGUNAAN SOFTWARE BAJAKAN DI KALANGAN MAHASISWA FTK UIN AR-RANIRY - Basrul Abdul Majid; Sari Vivianie; Bustami Yusuf (UIN Ar-Raniry, 2018)
The use of pirated computer software among univetrsity’s students today is very vulnerable. This is due to two factors, namely; 1) the lack of awareness of the students from type of software they use, 2) and also the lack of understanding of the students about halal-haram in using pirated software. In this study, the authors intends to know the awareness and understanding of computer users, especially among students of pirated software both in terms of impact, legal, or risk from the use of pirated software. The study involved 200 students of the Faculty of Tarbiyah and Teacher Training of Ar-raniry State Islamic University of Banda Aceh, as selected by random. The results of this study showed 36% of students do not understand about pirated software and almost 65% of students are not aware of the risks caused by the use of pirated software and the legal dangers of the use of pirated software. In addition 62% of students currently using pirated software want to switch to using original software or opensource software.